Transformation Of Islamic Boarding School Culture In The Digital Era: Collaboration Of Local Values And Global Competence - Maylinda Putri Maharani (International journal of technology and education research, 2025)
The cultural transformation of Islamic boarding schools in the digital era is an effort to adapt traditional Islamic educational institutions to rapid technological developments. This research aims to analyze how Islamic boarding schools can combine the local values that form their identity with global competencies that are relevant in the 21st century. With a focus on the integration of digital literacy, curriculum changes, and the use of technology in education and da'wah, this research shows that Islamic boarding schools not only adopt technology to expand the reach of learning and da'wah, but also maintain a balance between preserving Islamic values and local traditions. The results of this research show that Islamic boarding schools are able to use technology wisely, by emphasizing the use of technology that is in line with Islamic morals. Apart from that, Islamic boarding schools are also updating their curriculum to improve 21st century skills, such as digital literacy, foreign languages and critical thinking. This research concludes that Islamic boarding schools can be a model of Islamic education that is innovative and relevant to global demands without losing Islamic identity and local values.